Rethinking nasal tip support: A finite element analysis. (11th August 2014) - Shamouelian, David; Leary, Ryan P.; Manuel, Cyrus T.; Harb, Rani; Protsenko, Dmitriy E.; Wong, Brian J. F.
<x xml:space="preserve">Abstract</x> Objective We employ a nasal tip finite element model (FEM) to evaluate contributions of two of the three major tip support mechanisms: attachments between the upper and lower lateral cartilages and attachment of the medial crura to the caudal septum. Study Design The nasal tip FEM computed stress distribution and strain energy density (SED) during nasal tip compression. We examined the impact of attachments between the upper and lower lateral cartilages and the attachment of the medial crura to the caudal septum on nasal tip support. Methods The FEM consisted of three tissue components: bone, cartilage, and skin. Four models were created: A) control model with attachments present at the scroll and caudal septum; B) simulated disruption of scroll; C) simulated disruption of medial crura attachments to caudal septum; and D) simulated disruption of scroll and medial crura attachments to caudal septum. Spatial distribution of stress and SED were calculated. Results The keystone, intermediate crura, caudal septum, and nasal spine demonstrated high concentration of stress distribution. Across all models, there was no difference in stress distribution. Disruption of the scroll resulted in 1% decrease in SED. Disruption of the medial crura attachments to the caudal septum resulted in 4.2% reduction in SED. Disruption of both scroll and medial crural attachments resulted in 9.1% reduction in SED. Conclusion The nasal tip FEM is an evolving tool to study structural nasal tip dynamics and demonstrates the loss of nasal tip support with disruption of attachments at the scroll and nasal base. Level of Evidence N/A Laryngoscope, 125:326–330, 2015